Steep Slopes Music and change in the Highlands of Papua New Guinea - Gillespie, Kirsty (ANU Press, 2010)
The Duna live in a physical environment of steep slopes that are sometimes difficult to traverse. A stick of bamboo used as a prop goes a long way in assisting a struggling traveller. Similarly, the Duna live in a social and cultural environment of steep slopes, where the path on which they walk can be precarious and unpredictable. Songs, like the stick of bamboo, assist the Duna in picking their way over this terrain by providing a forum for them to process change as it is experienced, in relation to what is already known. This book is a musical ethnography of the Duna people of Papua New Guinea. A people who have experienced extraordinary social change in recent history, their musical traditions have also radically changed during this time. New forms of music have been introduced, while ancestral traditions have been altered or even abandoned. This study shows how, through musical creativity, Duna people maintain a connection with their past, and their identity, whilst simultaneously embracing the challenges of the present.